Association between hypoalbuminemia and complications after degenerative and deformity-correcting spinal surgeries: A systematic review and meta-analysis - Li, Xia; Li, Haidong; Huang, Shufeng; Pan, Yiping (Frontiers in Surgery, 2023)
Objective: The current review was designed to explore if hypoalbuminemia is associated with increased complications in patients undergoing spinal degenerative and deformities surgeries. Methods: The search for eligible studies was conducted on the databases of PubMed, Embase, Web of Science, and CENTRAL up to 20th June 2022. Complication rates were pooled to obtain odds ratio (OR) and 95% confidence intervals. Results: Thirteen studies were included. We found that hypoalbuminemia was significantly associated with increased risk of all complications (OR: 2.72 95% CI: 2.04, 3.63 I2=58% p<0.00001), mortality (OR: 7.73 95% CI: 3.81, 15.72 I2=0% p<0.00001), revision surgery (OR: 3.15 95% CI: 1.53, 6.48 I2=87% p=0.002), readmissions (OR: 1.96 95% CI: 1.29, 2.98 I2=23% p=0.02), surgical site infections (OR: 2.97 95% CI: 1.90, 4.63 I2=38% p<0.00001), wound complications (OR: 2.31 95% CI: 1.17, 4.56 I2=48% p=0.02), pulmonary complications (OR: 3.74 95% CI: 2.66, 5.26 I2=0% p<0.00001), renal complications (OR: 3.04 95% CI: 1.22, 7.54 I2=0% p=0.02), cardiac complications (OR: 4.33 95% CI: 2.14, 8.77 I2=0% p<0.0001), urinary tract infections (OR: 2.08 95% CI: 1.80, 2.41 I2=0% p<0.00001), and sepsis (OR: 4.95 95% CI: 1.87, 13.08 I2=64% p=0.01) as compared to those with normal albumin. Conclusion: Hypoalbuminemia is a significant risk factor for complications after spinal degenerative and deformity surgeries. Research is also needed on the role of nutritional support in improving outcomes after spinal degenerative and deformity surgeries.